Proceedings of the International Conference on Advanced Technology and Multidiscipline (ICATAM 2024) - Tahta Amrillah; Prihartini Widiyanti; Retno Sari; Purbandini Purbandini; Lilik Jamilatul Awalin (Atlantis Press International BV, 2024)
This is an open access book. Technology has revolutionized our world and daily lives, shaping a future that must harmonize with nature. Through innovations in green energy, low-emission transportation, and energy-efficient housing, technology holds the potential to significantly aid resource recovery and environmental preservation. However, we must always consider the societal impacts of technological advancements. It is crucial to strive for a balance, ensuring that our technological progress supports both humanity and the environment sustainably. The Faculty of Advanced Technology and Multidiscipline at Universitas Airlangga is dedicated to leading the way in the formulation of engineering and advanced technology solutions. This year, we are proud to host the 4th International Conference of Advanced Technology and Multidiscipline (ICATAM). This virtual scientific platform aims to unite academia, researchers, engineers, government bodies, non-governmental organizations, private sectors, industries, and consultants from around the world. Our goal is to foster connections, collaboration, and discourse within a safe and physically distanced framework.